Standardizing Smart Contracts for Regulatory Compliance in Cross-Border Payments - Rahman, Samiur (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Smart contracts—auto-executing digital agreements built on DLT (Distributed Ledger Technology), an emerging technology of blockchain—are revolutionizing cross-border payments by enhancing efficiency and automation. However, their widespread adoption is hindered by a fragmented regulatory landscape and legal uncertainties across jurisdictions. Therefore, to promote the urgency of regulatory governance of smart contract, this research advocates for the techno-legal standardization of smart contracts to ensure regulatory compliance in international financial transactions. It investigates how smart contracts can be designed to meet diverse legal requirements while maintaining technical adaptability, scalability, and interoperability. Drawing on interdisciplinary literature and qualitative methods—including expert interviews, surveys, and case studies—the study aims to develop a framework that balances innovation with legal certainty. Key challenges addressed include jurisdictional fragmentation, enforcement mechanisms, integration with legacy systems like SWIFT, and compliance with KYC/AML regulations. The research also examines emerging solutions such as decentralized identity frameworks, trusted oracles, and hybrid on-chain/off-chain models. By bridging the gap between law, technology, and finance, this study offers actionable insights for policymakers, financial institutions, blockchain developers, and international businesses. Ultimately, it contributes to the development of a standardized smart contract ecosystem that supports secure, efficient, and legally compliant cross-border payments.